Relationship between Workload and Job Satisfaction of Nurses in the Inpatient Installation of the Aceh Tamiang Regional General Hospital - Bambang Kurniawan; Asyiah Simanjorang; Nur Aini (Newinera Publisher, 2021)
The purpose of this study was to determine the relationship between workload and job satisfaction of nurses in the Young Inpatient Installation available for surgery at the Aceh Tamiang Regional General Hospital.This research is a cross sectional analytic survey type where the independent variable and the dependent variable are examined simultaneously. The population in this study were 30 nurses in the Young Inpatient Installation available for surgery at the Aceh Tamiang Regional General Hospital. The results of the bivariate analysis with the chi-square statistical test showed that there was a relationship between qualitative workload and job satisfaction of nurses with a p-value of 0.005 (p <0.05), there was a relationship between quantitative workload and job satisfaction of nurses with a p-value of 0.019 ( p <0.05) after the chi-square statistical test was performed. It is recommended to the Aceh Tamiang Regional Hospital for the placement of the need for nurses to be adjusted in quantity and quality to increase job satisfaction of the nurses in charge, to conduct surveys and analysis of job satisfaction periodically for evaluation as a basis for improving and improving employee performance from the aspect of job satisfaction of nurses, and for other researchers. It is hoped that they can carry out more specific research with other factors that can lead to job satisfaction of nurses related to different methods and data analysis.